The association between teat shape and clinical mastitis - M.E. Spellman; C.M. Geary; H. Somula; A. Singh; M. Wieland (Journal of Dairy Science)
ABSTRACT: Conformational teat traits such as teat-barrel shape and teat-end shape have long been recognized as possible risk factors for elevated somatic cell count and clinical mastitis in dairy cows. However, the association between udder health and these teat traits is still under debate. Our objective with this ambidirectional cohort study was to investigate the relationship between teat shape and the occurrence of clinical mastitis in dairy cows. For this purpose, we analyzed quarter-level data from 14,948 quarters of 3,913 Holstein cows from 1 commercial dairy farm in New York State. Cows were milked 3 times daily, housed in freestall pens, bedded with manure solids, and fed a TMR. Teat shape was assessed visually and classified based on teat-barrel and teat-end shape into 1 of 4 categories as follows: (1) triangular barrel and pointed teat end (TP), (2) square barrel and round teat end (SR), (3) square barrel, round teat end, and flat in the area of the teat orifice (SRF), and (4) square barrel and flat teat end (SF). Data on the occurrence of clinical mastitis were obtained from the dairy management software. To test the hypothesis that teat shape was associated with the occurrence of the first clinical mastitis event during the first 305 d in milk, a multivariable semiparametric proportional hazards model was built. Our results showed that teat shape was associated with the occurrence of clinical mastitis. Compared with SR, the clinical mastitis hazards (95% CI) were TP, 1.66 (1.25–2.19); SF, 1.58 (1.14–2.18); and SRF, 1.05 (0.88–1.26). We conclude that teat shape could be useful to identify cows at increased risk of clinical mastitis. This could allow farmers to employ targeted monitoring of these high-risk animals and develop management strategies that mitigate their risk.